Salinity Stress and Its Alleviation in Plants: A General Review - Priya Kushwaha,; Rahul Verma,; Amit Kumar Singh,; Pallavi Dixit, (International Journal of Scientific Research in Science and Technology, 2025)
Agricultural salinization is one of the major and long-lasting abiotic stresses, as it hinders plant growth and development leading to physiological abnormalities that endanger global food security. This is primarily the result of salt build-up in the soil caused by human activities, including irrigation, inadequate growing, and excessive fertilization. Nearly 147 million ha of land are at the risk of soil degradation, with water erosion contributing to 94 million (ha), salinity/alkalinities/acidification for 23 million (50%), water depletion/flooding for 14 million (60%); wind erosion for 9 million and 7 million ha of a combination of factors arising from different forces. In order to ensure food security for the increasing population, the Indian government has set a goal to restore 26 million hectares of degraded land, including those affected by salt, by 2030. It is estimated that almost 10% of the added land becomes saline every year, and by 2050, about 50% of the arable land would be caused by salt. High levels of Na+ and Cl- ions in the soil subdues overall plant growth through ion imbalance, osmotic stress, oxidative stress, reduces nutrient uptake, reduction in yield, and damage to lipids, protein and DNA. In response to salinity stress, plants have developed a range of adaptive mechanisms such as ion homeostasis, osmoprotection, polyamines, nitric oxide, phytohormones and antioxidative defence system. This reviews tells about epigenetic regulation of salinity stress and various mitigation process to combat salinity stress like physical method (leaching, flushing and scrapping), chemical methods (Gypsum, zeolites, biochar, compost, and organic amendments) and biological methods (phytoremidation, bioremediation by use of PGPR, salt-tolerant bacteria, mycorrhiza, cynobacteria, use to various nanoparticle and some biotechnical tools like use of genome wide-association studies, salt-tolerant genes, proteomics, metabolomics and transcriptomics).
Keywords: Phytoremidation; Proteomics; Metabolomics; Transcriptomics; Osmoprotection; Polyamines; Nitric oxide; Nanoparticle